2022
DOI: 10.5455/njcm.20200702052729
|View full text |Cite
|
Sign up to set email alerts
|

Menstruation: Is a Normal Phenomenon Perceived Normally in Early Adolescents: A Cross Sectional Study

Abstract: Introduction: Most Indian women believe that menstruation contaminates the body and makes it unholy. With this background, present study was proposed. Objectives: 1. To assess the effects of menstruation on routine activities in early adolescent girl students. To describe the perceptions regarding menstruation in early adolescent girl students. Methods: Present study was a cross sectional study carried out in slum and non-slum schools of a Sholapur city. Total study duration was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…For many of them, it was an unexpected surprise or shock to experience it for the first time. Sancheti and Shinde (2020) conducted a cross-sectional study and found that menstruation affects the self-esteem of girls (Sancheti & Shinde, 2020). Moreover, symptoms of depression, stress, anxiety, behavioural changes and lower confidence were noticed during menstruation (Deci & Ryan, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For many of them, it was an unexpected surprise or shock to experience it for the first time. Sancheti and Shinde (2020) conducted a cross-sectional study and found that menstruation affects the self-esteem of girls (Sancheti & Shinde, 2020). Moreover, symptoms of depression, stress, anxiety, behavioural changes and lower confidence were noticed during menstruation (Deci & Ryan, 2008).…”
Section: Discussionmentioning
confidence: 99%